TRAVEL WRITING: AN APPLICATION OF WRITING WORKSHOP TO ENHANCE STUDENTS’S CREATIVE WRITING - Margawati, Prayudias (Jurnal Pendidikan Bahasa dan Sastra, 2014)
Writing is often assumed as uneasy skill to either learn or teach. For students, they find it difficult to develop ideas in writing. On the other hand, teachers, many of them, only ready with the materials but confuse with the appropriate ways to teach. This paper intends to describe and discuss a method of teaching writing namely writing workshop to improve students’ writing skill through travel writing. Writing workshop proposed by Calkins that consists of mini lesson, work time, peer conferring and/or response groups, share sessions, and publication celebration is applied in writing class for methodological purposes. In mini lesson, teacher offers something to the class that is meant to introduce a writing strategy done at the beginning of the workshop. During work time point, students start their new piece of writing. Teacher moves among students conferring with them while checking their works. Peer conferences or response groups provide a forum for students to talk about works in progress. When students work in group, one of them could arrange his/ her group needs during the work time. A share session may be varied, one possible way is each group shares their process of writing to other students. At the end of writing class, student writers come together to publish and/ or celebrate their final work. The publication could be in the form of portfolio, students’ diary, blog, or others. Travel writing genre is chosen as it could develop students’ creativity in describing/ narrating their own stories during, let say holiday or things they used to see on the way home weekly or monthly. Furthermore, travel writing as the product of creative writing teaches the readers of values, characteristics, and way of life. Last but not least, a professional writing teacher should set the writing workshop components in variety ways to achieve effective running-class.